United Republic of Tanzania : Third Review Under the Policy Support Instrument and Request for Waivers and Modification of Assessment Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2012)
Tanzania's fiscal policy has been tightened owing to the deteriorating financing climate and rising inflation. The Bank of Tanzania has tightened its reserve money program for 2011/12, and domestic interest rates have risen sharply since mid-2011. The authorities are expanding Tanzania's electric power generation capacity and raising electricity tariffs. Tanzania has good prospects as a major producer of natural gas by the end of the decade. The authorities will identify the critical macroeconomic policies and institutions to successfully manage future gas wealth.